Dynamics of Social Capital In Management Of â€œAmartaâ€ Village Business Entities Post-Covid-19 Pandemic - Kemala Hayati; Juhari Sasmito Aji (PERSPEKTIF, 2022)
The Purpose Of This Study Is To Analyze The Dynamics Of Social Capital In The Management Of Village Business Entities Amarta. The Success Of Village Business Entities In Reviving The Post-Covid-19 Economy Is Closely Related To The Dynamics Of Social Capital. The Research Method Used Is A Qualitative Approach With Primary And Secondary Data. The Results Of The Analysis Show That The Social Capital Of Village Business Entities Amarta Has A Significant Impact On Village Economic Growth After The Covid-19 Pandemic, This Is Influenced By The Influence Of Social Capital From Component 1) Social Networks In The Form Of Ownership Of Common Goals Which Are Pursued Through Formal Discussions And Informal Discussions Involving The Community. 2) Norms, Namely Written And Unwritten Rules To Improve The Quality Of Village Business Entities Management. 3) Trust, Which Is Implemented In The Form Of Cooperation With Fellow Village Business Entities Management And The Application Of Openness In Efforts To Manage Village Business Entities. So The Social Capital Component Will Achieve The Output Of Improving The Performance Of Village Business Entities.